CARACTERIZAÇÃO DE GRUPOS FLORÍSTICOS E RELAÇÕES COM VARIÁVEIS AMBIENTAIS E ESPACIAIS EM UM REMANESCENTE DE FLORESTA OMBRÓFILA MISTA MONTANA - Grespan, Tiago (2016)
The purpose of this work was verify the formation of floristic groups, characterize its structures, investigate the presence of indicator species in the formed groups and evaluate possible relationships with environmental and spatial variables in a remaining of Araucaria forest. For this, we used data from a network of permanent plots of 25 hectares located in the National Forest of Irati, Paraná. In this research was used systematic sampling process, in an allocated drawing on the permanent plots, where were established 100 plots of 10 m x 10 m. Inside the plots were computed all individuals present in the area in the year 2014 with a diameter at breast height (DBH) greater than or equal to 10 cm. Soil samples in the depth 0-20 cm were collected for chemical and physical analysis, as well the information of altitude in each sample unit. Through of the cluster analysis, floristic groups were defined and carried out the Indicator Species Analysis to verify the existence of these in the formed groups. The Detrended correspondence analysis was used to summarize the structure of vegetation and check for environmental gradients in the study area. Then, it was used the multiple linear regression (Ordinary Least Squares - OLS) to evaluate the possible effects of environmental and spatial predictor variables on the distribution and abundance of the species considered indicators. The spatial variables were represented by MEMs (Moran Eigenvector Maps), also called spatial filters. In all, 638 individuals were found, distributed in 29 botanical families, 55 genera and 72 species. Among the species that characterize the forest structure can emphasize Araucaria angustifolia, Ocotea odorifera, Ilex paraguariensis, Ocotea porosa e Nectandra grandiflora. The most important families in the community were Lauraceae, Araucariaceae and Myrtaceae, this latter presented the highest richness. Through the abundance matrix of the most significant species in the vegetation it was possible to detect three floristic groupings, which reflect changes in the composition and structure of vegetation. These changes were not attributable to environmental predictor variables, but to the variables that were not measured in the study and that are structured in space, which possibly represent ecological mechanisms, such as direction of propagules dispersion, combined still with the structuring effect of the spatial dynamics of the community.